From objects to subjects: Repositioning teachers as policy actors doing policy work. (August 2018) - Ellison, Scott; Anderson, Ashlee B.; Aronson, Brittany; Clausen, Courtney
Abstract: Within policy discourses, teachers are positioned as objects of reform who enact policies under rational systems of observation and accountability and are, therefore, situated as de-professionalized actors lacking expert knowledge. This research project asks relatively straight-forward questions: If practicing teachers were given a voice in political debates over urban education policy and reform, what would they say? What macro-level policy problems would they identify as being important? Findings indicate the primary policy problems include S ystemic Inequity and B ad Policy. The primary policy solutions include, Schools as a Community Resource; Shared Decision-Making; Contextual Goals; and Time, Space and Resources . Highlights: Focus group interviews with teachers in urban schools. Goal to introduce teachers' perspectives into policy debate over school reform. Data analyzed with tools from qualitative content analysis. Two broad policy problems were identified. Four policy solutions identified.